Neuroticism as a covariate of cognitive task performance in individuals with tinnitus - Edwards, Holly M.; Jackson, James G.; Evans, Hannah (Frontiers in Psychology, 2022)
Previous studies have shown cognitive task performance to be affected by tinnitus severity, but also that the literature is conflicted. This study sought to identify neuroticism as a possible confound, since severe tinnitus distress is associated with higher levels of neuroticism. 78 participants (39 with and 39 without tinnitus) undertook two cognitive tasks. It was found that when undertaking a Stroop paradigm, controlling for neuroticism rendered previously significant results not significant. It was also found that neuroticism was not a significant covariate for a change blindness task. Gender, age, anxiety and depression were all controlled for, and future implications for the literature discussed.